Seed-aided green synthesis of metal-organic frameworks in water - Hao-Tian An; Xin Zhang; Chen Dong; Mu-Yao Lu; Rui Li; Yabo Xie; Lin-Hua Xie; Jian-Rong Li (Green Chemical Engineering, 2023)
Green synthesis of metal-organic frameworks (MOFs) in water with alleviated environmental influence and reduced cost is an essential step to transfer laboratory MOFs research to industrial application. Switching from the commonly used organic solvents to pure water encounters challenges of the poor solubility of organic linkers, slow reaction kinetics, and the formation of polymorphic products. So far, a universal MOFs synthetic strategy in water system has yet to be developed. This study reports the seed-aided synthesis of eleven MOFs with diverse compositions and structures while pure water serving as solvent. The corresponding reaction temperature and time of using this new strategy were reduced compared with original synthetic approaches, while the products maintain porous structure and high crystallinity. The success of this strategy relies on the addition of parent MOFs as seeds which could promote crystallization process by skipping the time-consuming induction period and avoiding the formation of polymorphic impurities.